Thymidylate synthase inhibitor raltitrexed can induce high levels of DNA damage in MYCN‐amplified neuroblastoma cells. Issue 7 (10th June 2020) - Yamashita, Ken; Kiyonari, Shinichi; Tsubota, Shoma; Kishida, Satoshi; Sakai, Ryuichi; Kadomatsu, Kenji
Abstract: MYCN gene amplification is consistently associated with poor prognosis in patients with neuroblastoma, a pediatric tumor arising from the sympathetic nervous system. Conventional anticancer drugs, such as alkylating agents and platinum compounds, have been used for the treatment of high‐risk patients with MYCN ‐amplified neuroblastoma, whereas molecule‐targeting drugs have not yet been approved. Therefore, the development of a safe and effective therapeutic approach is highly desired. Although thymidylate synthase inhibitors are widely used for colorectal and gastric cancers, their usefulness in neuroblastoma has not been well studied. Here, we investigated the efficacies of approved antifolates, methotrexate, pemetrexed, and raltitrexed (RTX), on MYCN ‐amplified and nonamplified neuroblastoma cell lines. Cell growth‐inhibitory assay revealed that RTX showed a superior inhibitory activity against MYCN ‐amplified cell lines. We found no significant differences in the protein expression levels of the antifolate transporter or thymidylate synthase, a primary target of RTX, among the cell lines. Because thymidine supplementation could rescue the RTX‐induced cell growth suppression, the effect of RTX was mainly due to the reduction in dTTP synthesis. Interestingly, RTX treatments induced single‐stranded DNA damage response in MYCN ‐amplified cells to a greater extent than in the nonamplified cells. We propose that the high DNA replication stress and elevated levels of DNA damage, which are a result of deregulated expression of MYCN target genes, could be the cause of increased sensitivity to RTX. Abstract : Deregulated expression of MYCN target genes results in high DNA replication stress and elevated levels of DNA damage, which in turn could be a cause of increased sensitivity to raltitrexed in MYCN ‐amplified neuroblastoma cell lines.